Comparative Analysis of Diel and Circadian Eclosion Rhythms and Clock Gene Expression Between Sexes in the Migratory Moth Spodoptera frugiperda - Changning Lv; Yibo Ren; Viacheslav V. Krylov; Yumeng Wang; Yuanyuan Li; Weidong Pan; Gao Hu; Fajun Chen; Guijun Wan (Insects, 2025)
The circadian clock orchestrates behavioral and molecular processes such as eclosion. Understanding eclosion timing may offer insights into circadian mechanisms underlying migratory timing. Here, we characterize the diel and circadian patterns of eclosion and core clock gene expression in the fall armyworm (FAW), Spodoptera frugiperda, a globally distributed migratory moth. Using a custom-designed eclosion monitoring system under 14 h light: 10 h dark (L14: D10) and constant darkness (DD) conditions, we observed robust diel eclosion rhythms peaking shortly after lights-off under L14: D10, which became delayed and damped over three consecutive days in DD. Males showed a tendency toward more dispersed emergence patterns and exhibited statistically distinguishable eclosion distributions from females under both conditions. Expression of five canonical clock genes (cyc, clk, tim, per, cry2) displayed significant 24 h rhythmicity, with generally higher mesors in males. However, sex-specific differences in amplitude and phase were detected only for clk and cyc under L14: D10, not in DD. These findings suggest that sex-specific differences in circadian regulation are limited. Nonetheless, subtle variations in clock gene output and emergence timing in the FAW population established in China may contribute to sex-specific ecological strategies in the novel migratory arena.